2001
DOI: 10.1128/iai.69.1.534-537.2001
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcal rofA Gene Is Involved in the Control of Several Virulence Genes and Eukaryotic Cell Attachment and Internalization

Abstract: The serotype M6 group A streptococcal RofA regulator was previously shown to exert a direct positive control of protein F1 expression and, concomitantly, fibronectin binding. Using a serotype M6 rofA mutant, we demonstrate here that this regulator has a potentially indirect negative influence on the expression of the mga, emm6, pel-sagA, and speA virulence genes. Additionally, the rofA mutant exhibited reduced eukaryotic cell internalization rates in combination with decreased host cell viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 36 publications
3
61
1
Order By: Relevance
“…The corresponding nra49 gene sequence (accession number U49397 ; Podbielski et al, 1999) exhibited only 62n6% sequence homology. The rofA2 gene was inactivated by insertion mutagenesis (Beckert et al, 2001) and the mutation was confirmed by PCR and Southern hybridization (data not shown). No differences in the growth rate and final optical cell density between wild-type and mutant was detected (data not shown).…”
Section: Construction Of a Rofa Mutant In The Gas Serotype M2mentioning
confidence: 92%
See 3 more Smart Citations
“…The corresponding nra49 gene sequence (accession number U49397 ; Podbielski et al, 1999) exhibited only 62n6% sequence homology. The rofA2 gene was inactivated by insertion mutagenesis (Beckert et al, 2001) and the mutation was confirmed by PCR and Southern hybridization (data not shown). No differences in the growth rate and final optical cell density between wild-type and mutant was detected (data not shown).…”
Section: Construction Of a Rofa Mutant In The Gas Serotype M2mentioning
confidence: 92%
“…All mutant strains were maintained on medium supplemented with 60 mg spectinomycin l − ". The RofA6 and Nra49 mutant strains have been described elsewhere (Beckert et al, 2001 ;Molinari et al, 2001). The EmmLuc recombinant strain was constructed in this study according to methods published by Podbielski et al (1999).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CodY, Irr, SLS and SptR regulate positively the operon [56][57][58][59] whereas CcpA, CovR, FasX, LuxS, Mga and RopB and members of the Ralp regulator family including RofA, Nra and Ralp3 have repressing effects. 42,56,57,[60][61][62][63][64][65][66][67][68][69][70][71] The nutritional status of the cells also has regulatory roles on sag/pel expression. 46,72 How Pel controls the expression of virulence factors has not yet been deciphered and no primary targets are known.…”
Section: Integration Of Srnas Into the Regulatory Network Of Streptomentioning
confidence: 99%